2005
DOI: 10.1074/jbc.m411860200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress in Insulin Resistance and Diabetes

Abstract: Type 2 diabetes is one of the most prevalent and serious metabolic diseases in the world, and insulin resistance and pancreatic ␤-cell dysfunction are the hallmarks of the disease. In this study, we have shown that endoplasmic reticulum (ER) stress, which is provoked under diabetic conditions, plays a crucial role in the insulin resistance found in diabetes by modifying the expression of oxygen-regulated protein 150 (ORP150), a molecular chaperone that protects cells from ER stress. Sense ORP overexpression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
296
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 414 publications
(320 citation statements)
references
References 17 publications
12
296
0
9
Order By: Relevance
“…Both 4-PBA and UDCA have been successfully used to alleviate ER stress, restore glucose tolerance and improve insulin sensitivity. 20,45,46 However, the effect of 4-PBA or UDCA on ER stress in DN remains un-elucidated. Our findings have shown that both UDCA and 4-PBA could suppress the UPR in podocytes in vitro, as evidenced by the decreased protein expression of BiP, phospho-PERK, phospho-IRE1α and cleaved ATF-6, which were upregulated by HG, suggesting that UDCA and 4-PBA could inhibit HG-induced ER stress in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both 4-PBA and UDCA have been successfully used to alleviate ER stress, restore glucose tolerance and improve insulin sensitivity. 20,45,46 However, the effect of 4-PBA or UDCA on ER stress in DN remains un-elucidated. Our findings have shown that both UDCA and 4-PBA could suppress the UPR in podocytes in vitro, as evidenced by the decreased protein expression of BiP, phospho-PERK, phospho-IRE1α and cleaved ATF-6, which were upregulated by HG, suggesting that UDCA and 4-PBA could inhibit HG-induced ER stress in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The ER is a complicated and systemic network, and excessive ER stress may result in insulin resistance [3,41,42] and islet β-cell dysfunction [43] . Currently, increasing chaperones has been reported to help improve insulin resistance [6] . Here we focused on ATF6 for its potent service as a critical signal transducer in the ER stress system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a special interest in ER stress because of its central role in the pathogenesis of type 2 diabetes, and valuable results have been discovered [3][4][5][6] . For example, it was found that molecular indicators of ER stress, such as PERK, eukaryotic initiation factor 2α (eIF2α) and glucoseregulated protein 78 (GRP78), increased in liver and adipose tissues of dietary and genetic murine obesity models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…type 2 diabetes mellitus is a complex disease characterized by insulin resistance and insufficient insulin secretion [10,11]. Recently, various studies have shown that eR stress plays a crucial role in the development of insulin resistance and the pathogenesis of type 2 diabetes [12][13][14][15][16][17][18][19]. X-box-binding protein-1 (XBP-1) is a key transcription factor in the eR stress a frameshift of the fusion mRna, and translation of the spliced mRna continues up to the stop codon of venus.…”
mentioning
confidence: 99%